Застосування акустичної емісії як одного з засобів технічного захисту - Німченко, Т. В. (НТУ "ХПІ", 2015)
Розглянуто використання методу акустичної емісії в системах технічного захисту інформації. Розглянуто структуру акустичних сповіщувачів руйнування скла. Представлено структуру блоку реєстрації та обробки сигналів акустичної емісії під час руйнування скла. Наведено схему підсилювального тракту сигналів аскустичної емісії та схему амплітудного детектора. Запропоновані апаратні засоби дозволяють реєструвати сигнал акустичної емісії з високою чутливістю.

The use of acoustic emission method in the technical data protection. The structure of acoustic detectors destruction glass. Shows the classification and stages of development. It is shown that acoustic detectors destruction glass for its operation using acoustic wave field generated in the destruction of protected glazed design. Summarizes the functional diagram of the acoustic detector destruction glass. The structure unit recording and processing of acoustic emission signals in the destruction of the glass. Shows a diagram of the amplifier signal path askustychnoyi emissions and peak detector circuit. It is shown that the amplitude detector consists of two main parts: the converter serednovypryamlenyh values and filter. The detector has a much smaller error, and the use of modern high-frequency operational amplifier helped to create it with high gain. The simulation package Electronics Workbench, allowing work to explore the amplitude detector with different characteristics of the input signal. It is shown that the proposed hardware allows to record acoustic emission signals with high sensitivity, with small dimensions through the use of modern SMD technology and a wide frequency range.
Application of acoustic emission as a means of technical protection
Keywords: охоронні системи; акустичні сповіщувачі; руйнування скла; сигнал АЕ; підсилювач; acoustic emission; security systems; technical security; power; destruction; detectors